The power of the Fortrex - Schmidt, Rebecca L (New York : Scholastic Inc., 2016)
Clay, who always does things by the knights' code handbook, and Lance, who would rather play video games than study a book on rules, must work together long enough to take down Jestro and his magma monsters.
Keywords: Knights and knighthood -- Fiction; Monsters -- Fiction; Science fiction; Fantasy